2012
DOI: 10.1097/inf.0b013e31824da7fe
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Risk Factors and Outcome of Candida parapsilosis Bloodstream Infection in Children

Abstract: Background Candida parapsilosis constitutes a common Candida spp. isolated in children with candidemia. Few data exist on risk factors and outcome of candidemia caused by C. parapsilosis in pediatric patients. Methods We conducted a retrospective analysis of demographic data, clinical features, therapeutic procedures and outcomes associated with Candida bloodstream infections (BSIs) that occurred at the Children’s Hospital of Philadelphia between 1997–2009. Results Among 406 Candida BSIs, Candida albicans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 24 publications
1
32
0
2
Order By: Relevance
“…12,14,24 In the MSGsponsored observational study, 12 the mean age of pediatric patients was only 8 months, which could explain why their Candida species distribution was more similar to that of our neonatal patients. We found that C. albicans was the most frequently occurring species, but non-albicans Candida species predominated overall.…”
Section: Discussionmentioning
confidence: 76%
“…12,14,24 In the MSGsponsored observational study, 12 the mean age of pediatric patients was only 8 months, which could explain why their Candida species distribution was more similar to that of our neonatal patients. We found that C. albicans was the most frequently occurring species, but non-albicans Candida species predominated overall.…”
Section: Discussionmentioning
confidence: 76%
“…Candida parapsilosis was the second‐most common isolated Candida species across all patients in the present study. Colonisation of infant skin by horizontal transmission from the colonised hands of health care workers who have direct contact with patients can lead to CVC‐related infection with C. parapsilosis . Its high ability to adhere to/form biofilm on foreign materials and grow on glucose‐ and amino acid‐rich parenteral nutrition solutions are the main risk factors for infections by this species .…”
Section: Discussionmentioning
confidence: 99%
“…While Candida albicans is the leading cause of invasive candidiasis in general, children under the age of 2 are at greater risk of infections caused by C. parapsilosis , an emerging non- albicans Candida species (Dotis et al, 2012; Juyal et al, 2013; Jordan et al, 2014). …”
Section: Introductionmentioning
confidence: 99%